PENGARUH PERAWATAN MENGGUNAKAN BALUTAN BASAH TERHADAP PENYEMBUHAN LUKA GANGREN DI PUSKESMAS MULIOREJO TAHUN 2020 - Megawati Megawati (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2020)
Treatment measures in patients with gangrene wounds are used to protect the underlying tissue and further damage in order to accelerate tissue formation. By: using semipermeable dressing to prevent dryness and maintain good tissue, not attached, impermeable to bacteria, able to maintain high humidity at the site of injury while also releasing excessive exudate. The purpose of this study was to determine the effect of treatment measures using wet dressing to accelerate the healing of Gangren Wounds in the Muliorejo Health Center. This type of research is Pre Experimental Design with One Shot Case Study design. The method of taking samples by means of Accidental Sampling and the results of research that has been done, the level of wound healing speed in Gangren Wound patients is to use a wet dressing with a value of 16-20 (fast) of 7 people while with a value of 1-15 (slow) of 3 person. From the results of a statistical test with a significant P <0.05 using computerized P values obtained: 0,000 which is smaller and 0.05 and it can be concluded that there is an influence of the wet dressing on the acceleration of healing of Gangren Wounds in the Muliorejo Public Health Center. Nursing care and continuing interventions using wet dressing as often as possible on gangrene wounds.Keywords: acceleration of healing, gangren wound, nursing care, intervention, wet wrap treatment